PEMBERDAYAAN KELUARGA DAN KADER KESEHATAN MELALUI PELATIHAN ACTIVE CYCLE BREATHING TECHNIQUE (ACBT) UNTUK MENINGKATKAN BERSIHAN JALAN NAPAS PADA PENDERITA TUBERKULOSIS PARU BERBASIS KOMUNITAS - Sumitro Sumitro; Okti Rahayu Asih; Desty Lismayanti; Sarini Sarini; Yanti Rosmiyanti; Cindy Desriant (Bajang Institute, 2025)
Pulmonary tuberculosis (TB) remains a major public health challenge in Indonesia, requiring not only pharmacological treatment but also community-based supportive interventions to improve patient recovery. One of the non-pharmacological interventions that can be implemented is the Active Cycle Breathing Technique (ACBT), which helps enhance airway clearance, facilitate sputum expectoration, and improve respiratory function. This community service program aimed to empower family members and community health volunteers (cadres) through education and hands-on training on the implementation of ACBT to support home-based care for pulmonary TB patients. The program adopted a Participatory Learning and Action (PLA) approach involving 30 participants consisting of family caregivers and community health cadres. Activities included health education, demonstrations, supervised practice, simulation sessions, home-based mentoring, and program evaluation using pretest–posttest assessments and practical skill observations. The results demonstrated a substantial improvement in participants' knowledge and practical skills regarding ACBT implementation. Most participants were able to perform the breathing exercises correctly and confidently assist TB patients in conducting regular respiratory rehabilitation at home. Furthermore, the involvement of community health cadres strengthened community participation and promoted sustainable patient support beyond healthcare facilities. The program also increased participants' awareness of the importance of family involvement in tuberculosis management and reinforced collaboration between families, health workers, and local communities. Therefore, empowering families and community health cadres through ACBT training represents an effective community-based strategy to complement medical treatment, improve respiratory rehabilitation, enhance patients' quality of life, and support national tuberculosis control efforts